A case report of Carotid Blow-Out Syndrome whilst driving: A cautionary reminder of the Driver and Vehicle Licensing Agency (DVLA) regulations - Anika Patel; Mandeep Bajwa; Owais Khattak (Elsevier, 2021)
Carotid Blow-Out Syndrome (CBS) is a life-threatening complication of head and neck cancer. We report the case of a patient who suffered a fatal haemorrhage whilst driving, review the law and role of healthcare professionals in preventing such events.